Local authorities and the school system: The new authority-wide partnerships. (May 2014) - Hatcher, Richard
Coalition government policies have put into question the role of local authorities in a 'self-improving school system'. In a number of local authorities new authority-wide partnership bodies are being set up involving all local schools, including academies, and controlled by headteachers. This article begins with an analysis of the new partnerships, differentiating their functions and the education policy leadership roles of headteacher-led and local authority-led partnerships. It then examines as a case study the evolution of a new partnership in Birmingham from the initial model proposed by the local authority through to the emergence of a headteacher-initiated model. The article proposes an analytical framework for the new partnerships, situating them in the wider theoretical context of network governance and the role of the state in local government theory and policy. It concludes with a discussion of the questions of educational principle about agency and purpose in local education policymaking which the new partnership developments raise.